Isoniazid subverting erythrocyte homeostasis: implications for tuberculosis therapy - Sikandar, Muhammad; Fatima, Maria; Jilani, Kashif; Xing, Li (Frontiers in Pharmacology, 2026)
Isoniazid (INH) is a frontline anti-tuberculosis drug. Understanding the molecular mechanisms by which INH affects antioxidant defence in human blood cells, particularly erythrocytes vulnerable to oxidative damage, remains essential to improving therapy safety. Here, the transcriptomic data of tuberculosis INH therapy-treated HepG2 cell line were analyzed to identify differentially expressed genes (DEGs). DEGs were cross-referenced with curated oxidative stress (OS) gene sets from GeneCards, and protein-protein interaction (PPI) networks were constructed to identify hub OS genes associated with INH treatment-induced OS. Biochemical assays assessed antioxidant enzyme activities (SOD, GPx, CAT and ROS), erythrocyte morphology, membrane integrity, and calcium involvement following INH exposure in vitro. A total of 7202 DEGs were identified, with 196 overlapping OS-related genes forming a focused gene set. Key hub genes, including SOD1, SOD2, and GPx family members, were downregulated, corresponding to decreased antioxidant enzyme activities in erythrocytes exposed to INH (3–6 mM). Functional analysis highlighted upregulation of oxidative stress response pathways and upregulation of cell adhesion/survival pathways such as the IL17 signalling pathway. INH induced erythrocyte membrane blebbing and mean cell volume expansion, which was attenuated by calcium channel blockade, indicating Ca2-dependent mechanisms driving membrane destabilization. Haemolysis assays confirmed concentration-dependent erythrocyte fragility. The results show that INH may disrupt erythrocyte redox balance by suppressing critical antioxidant enzymes and activating OS pathways, leading to cellular dysfunction and membrane instability mediated by calcium influx. These findings integrate transcriptomic insights with biochemical validation, underscoring the importance of monitoring oxidative damage in patients undergoing INH therapy.